Djibouti : Fourth Review Under the Extended Credit Facility Arrangement and Request for Waivers of Nonobservance of Performance Criteria: Staff Report and Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The fourth review of Djibouti's economic performance under the Extended Credit Facility (ECF) arrangement highlights that the authorities maintained fiscal discipline in 2010, but fiscal performance weakened in the first months of 2011. The authorities made progress toward tackling high input costs, which hinder the development of the private sector. The Djibouti authorities remain committed to the IMF program, especially in the areas of fiscal discipline and structural reforms in tax revenue, public financial management, bank supervision, and central bank governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet